Corporate social responsibility reporting - necessity or fashion - Władysław Świątek (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The current legislation, rules and procedures for reporting data referring to the situation of enterprises do not provide full information necessary to make decisions. This study attempts to present corporate social responsibility reports as an element reducing the so-called gap in value between the book value and market value of enterprises. The benefits and threats resulting from reporting social attitudes and their impact on the perception of the company by stakeholders are also presented.